PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN CABANG LANGSA - Surya Darma (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
In an increasingly complex and ever-changing business environment, the study of leadership can no longer be as simple as using these two dimensions. Likewise, efforts to find the best leadership style that applies throughout time will be in vain. There is a need to find a leadership model that is more relevant to complex situations like today. Transformational leadership is one of the "breakthrough" concepts that has revived the passion of leadership studies that have almost died over the past decade. Motivation can also be interpreted as providing a driving force that creates the excitement of one's work to be willing to work together, work effectively and be integrated with all their efforts to achieve satisfaction. From the results of the identification of the problems above, the problem can be formulated as follows: How is the influence of Transformational Leadership on the Performance of BPJS Health Officers in Langsa Branch. As for the Results of this Research Performance = 24,007 C +, 195 X1 +, 016 X2 +, 214 X3 explanation can be described as follows: Constant value of 24.007 means that if the overall value of the variable (SinismeX1, Emotional IntelligenceX2, Work StressX3) rises by 1a respectively, the Performance value (Y) will rise to 24.007. Cynic coefficient value of 0.195 means that if the value of Cynicism increases by 1a, the performance value will also increase by 0.195. Positive coefficient value means that Cynicism has a positive influence on performance. The value of the Emotional Intelligence coefficient of 0.016 means that if the value of Emotional Intelligence rises by 1a, the performance value will also increase by 0.016. A positive coefficient value means that Emotional Intelligence has a positive influence on Performance. The value of the Job Stress coefficient of 0.214 means that if the value of Job Stress rises by 1a, the performance value will also increase by 0.214. A positive coefficient value gives the meaning that Job Stress gives a positive influence on Performance.